PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN YANG DIMEDIASI OLEH PENGUNGKAPAN SUSTAINABILITY REPORT - Susanti Widhiastuti; Eftianto Eftianto; Slamet Ahmadi (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2019)
This study aims to determine the effect of financial performance, on the value of the company with disclosure of sustainability report as a mediating variable. The population in this study are companies listed on the Indonesia Stock Exchange and consistently included in the SRI-KEHATI Index from 2012-2016 as many as 19 companies. The selection of samples using purposive sampling method and the sample used in this study amounted to 14 companies for 5 years. The method of analysis uses multiple regression. The results showed that profitability and liquidity as a measure of the company's financial performance did not affect the disclosure of sustainability bother while the solvency had an effect on disclosure of sustainability bother. Profitability and solvency affect the value of the company, but liquidity and sustainability report disclosure do not affect the value of the company. This study also shows that sustainability report disclosure cannot mediate the effect of financial performance on firm value. Keywords: Financial Performance, Sustainability Report, Company Value